Bahasa Jargon Waria di Kawasan Kronjo Tangerang dalam Kajian Sosiolingustik - Fauzi, Aziz; Suta Wardianto, Bayu (Universitas Veteran Bangun Nusantara, 2022)
This study examines the use of jargon language that has been used by waria groups in the Kronjo area, Tangerang Regency, Banten. The data is in the form of speech that is used when interacting in general. The waria uses two languages or bilinguals, namely Javanese and Indonesian. This research has a purpose; (1) classifying the use of jargon language in waria in the Kronjo Tangerang area; (2) explain the form of jargon language use in waria in the Kronjo Tangerang area. In addition, this study also uses descriptive qualitative methods. The data taken by the researchers was carried out on June 27 and July 4, 2021. The place where the interview was conducted at Salon Mimi, the place was addressed in Kampung Daon, Bakung Village RT25 / RW 06. Kronjo Subdistrict, Tangerang Regency, Banten Province. As for the results of the interview, the researcher classified the form of jargon into three categories. First the jargon data is in the form of words; both jargon data are abbreviated; all three jargon data are in the form of acronyms. The overall data collected 35 jargons with the following classifications: (a) word forms in jargon as many as 22 data; (b) the abbreviation form in jargon of 6 data; (c) the form of an acronym in jargon as 7 data.